Influence of Coach’s Anger on Team’s Performance in Basketball - Víctor Hugo Duque Ramos; Álvaro Correa Martín; Miguel Ángel Gómez Ruano; Pedro Sáenz-López Buñuel, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
Coaches exert a significant influence on team enviroment as well as on the collective performance in team sports. Based on these premises, this study aims to analyze the effects of the coaches’ anger on the basketball teams’ performance in youth players. The study sample was composed by 24 basketball matches of the semifinals and finals of the Spanish Championship of Autonomous Teams for Under-16 (U16) and under-14 (U14) male and female players during the years 2019 and 2020. Every game was video observed using an ad hoc observational instrument. A total of n=544 anger events from the coaches of all 32 teams were analysed. The results showed a higher frequency of anger in the U14 category, in female players, in teams that were losing and when the result was close. Most anger actions seem to have a negative or neutral effect on team’s performance. It is particularly negative when it is focused on the referee, who is the main cause and object of the anger. When coaches showed low intensity anger, they obtained slight improvements. The results suggest that coaches need to manage and control their emotions according to the game context.